Zoon balanitis: A comprehensive review - Dayal, Surabhi (Indian J Sex Transm Dis AIDS, 2016)
The diagnosis and management of nonvenereal diseases are always a tough challenge for the dermatologist due to lack of studies on its diagnostic criteria and standard treatment guidelines. Zoon balanitis (ZB) is one of the benign nonvenereal dermatoses, which presents as a solitary, persistent erythematous plaque usually on the glans penis primarily in the uncircumcised, middle-aged to old-aged men. Although it was described by Zoon in 1952, its etiopathogenesis still remains hypothetical. This article provides an overview of the epidemiology, clinical presentation, histopathological features, and diagnostic criteria and diagnostic methods of ZB. In addition to this, it is rather very important to differentiate this lesion from its clinical equivocal lesions such as erythroplasia of Queyrat, infective and other inflammatory penile dermatoses, which has been discussed in this review. The treatment modalities have also been reviewed in details, and the importance of circumcision as the treatment of choice has been emphasized.